Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

The pathogenic responses elicited during exposure of human intestinal cell line with Giardia duodenalis excretory-secretory products and the potential attributed endocytosis mechanism - Xiran Yu; Yongwu Yang; Weining Zhu; Min Liu; Jingxue Wu; Steven M. Singer; Wei Li (Medical Microbiology and Immunology, 2024)

New perspectives on ice forcing in continental arc magma plumbing systems - Brad S. Singer; Pablo Moreno-Yaeger; Meredith Townsend; Christian Huber; Joshua Cuzzone; Benjamin R. Edwards; Matias Romero; Yasmeen Orellana-Salazar; Shaun A. Marcott; Rachel E. Breunig; Ken L. Ferrier; Kathryn Scholz; et al. (Journal of Volcanology and Geothermal Research, 2024)

Revealing oxidative pentose metabolism in new Pseudomonas putida isolates - Mee‐Rye Park; Rahul Gauttam; Bonnie Fong; Yan Chen; Hyun Gyu Lim; Adam M. Feist; Aindrila Mukhopadhyay; Christopher J. Petzold; Blake A. Simmons; Steven W. Singer (Environmental Microbiology, 2023)
The Pseudomonas putida group in the Gammaproteobacteria has been intensively studied for bioremediation and plant growth promotion. Members of this group have recently emerged as promising hosts to convert intermediates derived from plant biomass to biofuels and biochemicals. However, most strains of P. putida cannot metabolize pentose sugars derived from hemicellulose. Here, we describe three isolates that provide a broader view of the pentose sugar catabolism in the P. putida group. One of these isolates clusters with the well‐characterized P. alloputida KT2440 (Strain BP6); the second isolate clustered with plant growth‐promoting strain P. putida W619 (Strain M2), while the third isolate represents a new species in the group (Strain BP8). Each of these isolates possessed homologous genes for oxidative xylose catabolism ( xylDXA ) and a potential xylonate transporter. Strain M2 grew on arabinose and had genes for oxidative arabinose catabolism ( araDXA ). A CRISPR interference (CRISPRi) system was developed for strain M2 and identified conditionally essential genes for xylose growth. A glucose dehydrogenase was found to be responsible for initial oxidation of xylose and arabinose in strain M2. These isolates have illuminated inherent diversity in pentose catabolism in the P. putida group and may provide alternative hosts for biomass conversion.

Local groundwater decline exacerbates response of dryland riparian woodlands to climatic drought - Jared Williams; John C. Stella; Steven L. Voelker; Adam M. Lambert; Lissa M. Pelletier; John E. Drake; Jonathan M. Friedman; Dar A. Roberts; Michael Bliss Singer (Global Change Biology, 2022)
Dryland riparian woodlands are considered to be locally buffered from droughts by shallow and stable groundwater levels. However, climate change is causing more frequent and severe drought events, accompanied by warmer temperatures, collectively threatening the persistence of these groundwater dependent ecosystems through a combination of increasing evaporative demand and decreasing groundwater supply. We conducted a dendro‐isotopic analysis of radial growth and seasonal (semi‐annual) carbon isotope discrimination (Δ 13 C) to investigate the response of riparian cottonwood stands to the unprecedented California‐wide drought from 2012 to 2019, along the largest remaining free‐flowing river in Southern California. Our goals were to identify principal drivers and indicators of drought stress for dryland riparian woodlands, determine their thresholds of tolerance to hydroclimatic stressors, and ultimately assess their vulnerability to climate change. Riparian trees were highly responsive to drought conditions along the river, exhibiting suppressed growth and strong stomatal closure (inferred from reduced Δ 13 C) during peak drought years. However, patterns of radial growth and Δ 13 C were quite variable among sites that differed in climatic conditions and rate of groundwater decline. We show that the rate of groundwater decline, as opposed to climate factors, was the primary driver of site differences in drought stress, and trees showed greater sensitivity to temperature at sites subjected to faster groundwater decline. Across sites, higher correlation between radial growth and Δ 13 C for individual trees, and higher inter‐correlation of Δ 13 C among trees were indicative of greater drought stress. Trees showed a threshold of tolerance to groundwater decline at 0.5 m year −1 beyond which drought stress became increasingly evident and severe. For sites that exceeded this threshold, peak physiological stress occurred when total groundwater recession exceeded ~3 m. These findings indicate that drought‐induced groundwater decline associated with more extreme droughts is a primary threat to dryland riparian woodlands and increases their susceptibility to projected warmer temperatures.

Improvements in brain and behavior following eradication of hepatitis C - Taylor Kuhn; Philip Sayegh; Jacob D. Jones; Jason Smith; Manoj K. Sarma; A. Ragin; Elyse J. Singer; M. Albert Thomas; April D. Thames; Steven A. Castellon; Charles H. Hinkin (Journal of NeuroVirology, 2017)

Comparison of the Chemical Compositions of the Cuticle and Dufour’s Gland of Two Solitary Bee Species from Laboratory and Field Conditions - Theresa L. Pitts-Singer; Marcia M. Hagen; Bryan R. Helm; Steven Highland; James S. Buckner; William P. Kemp (Journal of Chemical Ecology, 2017)

Genomic Analysis of Xylose Metabolism in Members of the Deinoccocus-Thermus Phylum from Thermophilic Biomass-Deconstructing Bacterial Consortia - Yu-Wei Wu; Chijioke Joshua; Stephanie A. Eichorst; John M. Gladden; Blake A. Simmons; Steven W. Singer (BioEnergy Research, 2015)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Strategies for Enhancing the Effectiveness of Metagenomic-based Enzyme Discovery in Lignocellulolytic Microbial Communities - Kristen M. DeAngelis; John M. Gladden; Martin Allgaier; Patrik D’haeseleer; Julian L. Fortney; Amitha Reddy; Philip Hugenholtz; Steven W. Singer; Jean S. Vander Gheynst; Whendee L. Silver; Blake A. Simmons; Terry C. Hazen (BioEnergy Research, 2010)

New insights into the mechanism of nickel insertion into carbon monoxide dehydrogenase: analysis of Rhodospirillum rubrum carbon monoxide dehydrogenase variants with substituted ligands to the [Fe3S4] portion of the active-site C-cluster - Won Bae Jeon; Steven W. Singer; Paul W. Ludden; Luis M. Rubio (JBIC Journal of Biological Inorganic Chemistry, 2005)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)